2022
DOI: 10.1007/s12144-021-02549-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with general well-being among Lebanese adults: The role of emotional intelligence, fear of COVID, healthy lifestyle, coping strategies (avoidance and approach)

Abstract: General well-being is best described as the state of mind that gives people happiness and satisfaction in life. This concept is influenced by behaviors and attitudes that individuals do on a daily basis. The purpose of this study was to understand how general well-being is correlated with other factors such as emotional intelligence, Covid-19-induced fear, healthy lifestyle, and coping strategies. This cross-sectional study was carried out between December 2020 and January 2021 during the COVID-19 pandemic whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…Personal care, in this study, was defined by engaging in healthy behaviours such as healthy eating and sufficient hydration, exercising, adequate sleep, as well as relaxing and engaging in meditative practices. Greater measures of healthy ways of life, personal hygiene, and relaxation practices such as these have been associated with higher reported wellbeing and reduced stress, indicating that these are helpful ways of reducing pandemic-related tension across different cultures including Germany, Lebanon, and the US [ 6 , 21 , 22 , 31–33 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Personal care, in this study, was defined by engaging in healthy behaviours such as healthy eating and sufficient hydration, exercising, adequate sleep, as well as relaxing and engaging in meditative practices. Greater measures of healthy ways of life, personal hygiene, and relaxation practices such as these have been associated with higher reported wellbeing and reduced stress, indicating that these are helpful ways of reducing pandemic-related tension across different cultures including Germany, Lebanon, and the US [ 6 , 21 , 22 , 31–33 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study argued COVID-19 stress could be increased by perfectionism (Pereira et al, 2022). Previous research on the Lebanese population suggests that individuals with a high level of fear from COVID-19 were significantly correlated with lower general wellbeing (Rahme et al, 2021;Sfeir et al, 2022) and more mental health issues (El Othman et al, 2021).…”
Section: Perfectionism Social Phobia Life Satisfactionmentioning
confidence: 99%
“…Additionally elevated psychological stress levels, anxiety and depression were reported among people who were in contact with COVID‐19 patients and those who were always up‐to‐dated on the news regarding this virus in a Lebanese cross‐sectional study (El Othman et al, 2021). The COVID‐19 pandemic poses a threat to patients with the obsessive–compulsive disorder which impacts their quality of life and mental health (Rahme et al, 2021), as well as lower general wellbeing (Sfeir et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As trait self-esteem is considered to be a stable overtime it might not change immediately after challenging situations. Previous research has indeed found significant associations between the above-mentioned challenges in Lebanon with mental health aspects and mental health disorders [86][87][88][89]. This could, in some way, explain how state selfesteem -that can be changeable from one context to another -mediated the association of religiosity and ON.…”
Section: Discussionmentioning
confidence: 75%